VARIASI MODEL LEFT-RIGHT SYMMETRY DALAM FISIKA PARTIKEL DAN KESESUAIANNYA TERHADAP ANOMALI CHIRAL - Maulana, Qidir; Satriawan, Mirza (BERKALA FISIKA, 2013)
It has been done variation left-right symmetry model in particle physics that depend onL R I SU(2) âŠ—SU(2) âŠ—U(1) gauge. With assumption leptons and quarks sector massformation is different, so we introducing new particles in quarks sector , , , L L R U D U and R D .From this idea will be examined chiral anomaly to decide are this variation model can becandidate besides standard model of particle physics.Keywords : left-right symmetry model, chiral anomaly